ANTESEDEN DAN KONSEKWENSI DARI CORPORATE IMAGE PADA USAHA KECIL MENENGAH / UKM - Sri Vandayuli Riorini; Christina Catur Widayati (MIX: JURNAL ILMIAH MANAJEMEN, 2014)
Abstract: The purpose of this study was to analyze the effect of an integrated Service quality, corporate image of the Purchase intentions. Respondents were used as samples in this study were 200 consumers SME bike shop. Purposive sampling technique using sampling and methods of data analysis using SEM technique. The results found that (1) the positive effect of the Corporate Service quality image, Purchase intentions, (2) thepositive effect of corporate image on Purchase Intention, and (3) Corporate imagemerupakan mediator in the relationship between the Service qualitydengan Purchase intentions.Penelitian further recommended to add the variable of Corporate social Responsibility / CSR as a factor affecting Purchase intention.Keyword: Service Quality, Corporate Image, Purchase Intentions, Small andMedium Enterprises / SME‘s